Innovation, tourism and territory : the challenges of peripheral regions : the case of Cova da Beira, Portugal - Santos, Domingos (2009)
The subject on innovation is nowadays central either to modern theories of regional development, either to the promotion of the tourimsm industry. Innovation, broadly defined to include not only product or process upgrading but primarily organizational and institutional rearrangements, is vital for regions and enterprises to obtain competitive advantages. During the last decade there has been a shift towards the understanding of the innovation process as a socially constructed mechanism based on the accumulation of knowledge (codified or tacit) through a continuous and interactive learning course. Territorial and firm competitiveness have, nowadays more than ever before, to deal with knowledge creation and with the development of localized capabilities able to promote learning processes. In this sense, the innovation dynamics is based on resources that are place-specific; so, regionally based complexes of innovation and production are increasingly the privileged instruments to harness and recreate knowledge and intelligence across the globe. One the fastest growing economic sector is nowadays the tourism activities. The purpose of the current paper is to provide, for one side, a critical state-of-the-art review of current research on innovation, either at territorial level, either whithin the tourism sector; for the other side the paper also aims to analyse the relation between entrepreneurial dynamics on the tourism sector and regional innovation theories, in a specific portuguese territory (the Cova da Beira region) with development difficulties. A special attention will be put on the firm and institutional characteristics of low density peripheral areas that have comparative advantages on tourism. Arguably, the promotion of territorially embedded tourist regional innovation systems in peripheral areas seems a fundamental and coherent strategy to face contemporary regional development challenges, as long-term regional competitiveness and sustainability has less to do with cost-efficiency and more to do with the ability of firms and institutions to innovate, i.e. to improve their knowledge base.